9(u+6)=-5u-30

Simple and best practice solution for 9(u+6)=-5u-30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(u+6)=-5u-30 equation:


Simplifying
9(u + 6) = -5u + -30

Reorder the terms:
9(6 + u) = -5u + -30
(6 * 9 + u * 9) = -5u + -30
(54 + 9u) = -5u + -30

Reorder the terms:
54 + 9u = -30 + -5u

Solving
54 + 9u = -30 + -5u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '5u' to each side of the equation.
54 + 9u + 5u = -30 + -5u + 5u

Combine like terms: 9u + 5u = 14u
54 + 14u = -30 + -5u + 5u

Combine like terms: -5u + 5u = 0
54 + 14u = -30 + 0
54 + 14u = -30

Add '-54' to each side of the equation.
54 + -54 + 14u = -30 + -54

Combine like terms: 54 + -54 = 0
0 + 14u = -30 + -54
14u = -30 + -54

Combine like terms: -30 + -54 = -84
14u = -84

Divide each side by '14'.
u = -6

Simplifying
u = -6

See similar equations:

| 0.30x+0.05(8-x)=0.10(-36) | | 129-8x=8x+15 | | 27x^2-75= | | Y=3x^2-12x+8 | | 42x+36x^2= | | 0.20x+0.15(50)=22.5 | | 0.9x-0.3(10-3x)=-0.1(x-8) | | -6x+6=-4(x-4) | | 7x-x-x+10=2-3n | | -2(4x+2y)=-2(6) | | 5c^2-50c+105=0 | | 6x(6x+7)= | | 0.6x+5.5=4.6 | | 2x^2-6+4=0 | | -7-4x=11-7 | | 19x-4x+23=8x-19 | | 4u+4=-20 | | 2=6p-b-5p | | 8(w-4)-5w=-20 | | 2*x(7x+9)= | | -6+w/2=-4 | | 3x+2(x+8)=-14 | | 2=6p-8-5 | | 14y^2+7x^3+49y= | | (3y+1)20= | | 11=3y+4(y+8) | | 3(v-5)+2v=5 | | 4(5x+4)+36=13x-4 | | 0.6t-00.2+0.1t=0.4 | | 14y^2+7x^3+49y=7 | | 1.2(p-0.2)=-1.4 | | 88-3x=24+5x |

Equations solver categories